Potassium permanganate as an oxidizing and flocculating agent in groundwater treatment = Manganian (VII) potasu jako utleniacz i flokulant w oczyszczaniu wód podziemnych - Krupińska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The effectiveness of groundwater treatment with a high amount of organic substances and general iron depended on the kind of oxidizing agent, the kind and dose of coagulant, and the time of sedimentation. The effectiveness of the sedimentation process increased with the length of time of the process, and its results depended most on the method of oxidizing Fe(II).
Keywords: oczyszczanie wód podziemnych; koagulacja; utleniacze; potassium permanganate; groundwaters; coagulation